Temple and Postauricular Dissection in Face and Neck Lift Surgery - Lee, Joo Heon; Oh, Tae Suk; Park, Sung Wan; Kim, Jae Hoon; Tansatit, Tanvaa (Archives of Plastic Surgery, 2017)
Periauricular paresthesia may afflict patients for a significant amount of time after facelift surgery. When performing face and neck lift surgery, temple and posterior auricular flap dissection is undertaken directly over the auriculotemporal, great auricular, and lesser occipital nerve territory, leading to potential damage to the nerve. The auriculotemporal nerve remains under the thin outer superficial fascia just below the subfollicular level in the prehelical area. To prevent damage to the auriculotemporal nerve and to protect the temporal hair follicle, the dissection plane should be kept just above the thin fascia covering the auriculotemporal nerve. Around the McKinney point, the adipose tissue covering the deep fascia is apt to be elevated from the deep fascia due to its denser fascial relationship with the skin, which leaves the great auricular nerve open to exposure. In order to prevent damage to the posterior branches of the great auricular nerve, the skin flap at the posterior auricular sulcus should be elevated above the auricularis posterior muscle. Fixating the superficial muscular aponeurotic system flap deeper and higher to the tympano-parotid fascia is recommended in order to avoid compromising the lobular branch of the great auricular nerve. The lesser occipital nerve (C2, C3) travels superficially at a proximal and variable level that makes it vulnerable to compromise in the mastoid dissection. Leaving the adipose tissue at the level of the deep fascia puts the branches of the great auricular nerve and lesser occipital nerve at less risk, and has been confirmed not to compromise either tissue perfusion or hair follicles.
Keywords: Keywords; Rhytidoplasty; Paresthesia